Physical And Antioxidant Properties Of Cassava-based Rice Analogue - Ahmad Tamezi, Raihan Amani (Universiti Sains Malaysia, 2021)
Cassava-based rice analogue is a type of artificial rice made from cassava components that may be used as a healthy alternative diet for daily consumption due to high-quality nutrients and specific helpful properties that are beneficial to one's health. Consumers have now shifted toward healthier food options due to the rise in non-communicable diseases and unhealthy eating habits, but the current rice products on the market still do not provide a wide variety of choices to meet consumer needs. This research aims to study the physical and antioxidant properties of cassava-based rice analogue based on different substitution ratios of rice flour (RF) with modified cassava flour (MOCAF) which were 100:0, 70:30, 50:50, 30:70, and 0:100 followed with varied additions of cassava leaves flour (0 %, 10 %, and 20 %). Colour, total phenolic content (TPC), DPPH and FRAP scavenging activities, total tannin content (TTC) and total chlorophyll content (TCC) were all analysed. The result obtained showed that the substitution of RF with MOCAF and the addition of leaves had an effect on the physical and antioxidant properties in rice analogue formulation (RAF).